Essentials of pharmacology for health occupations - Woodrow, Ruth (Thomson Delmar Learning, 2007)
Basic and practical, this essential book provides an extensive framework of drug information in a concise format for allied health learners. Learn calculations quickly through a simplified step-by-step process. Discover key drug information by classifications, such as their purpose, side effects, cautions, and interactions, or utilize the resource to refresh your knowledge of drugs. Plug in the free accompanying CD-ROM and master pharmacology through quizzes, games, and case studies. Open this resource now and see how easy learning pharmacology can be.